Population Genomics of Mycobacterium leprae Reveals a New Genotype in Madagascar and the Comoros - Avanzi, Charlotte; Lécorché, Emmanuel; Rakotomalala, Fetra Angelot; Benjak, Andrej; Rapelanoro Rabenja, Fahafahantsoa; Ramarozatovo, Lala S.; Cauchoix, Bertrand; Rakoto-Andrianarivelo, Mala; Tió-Coma, Maria; Leal-Calvo, Thyago; Busso, Philippe; Boy-Röttger, Stefanie; et al. (Frontiers in Microbiology, 2020)
Human settlement of Madagascar traces back to the beginning of the first millennium with the arrival of Austronesians from Southeast Asia followed by migrations from Africa and Middle East. Remains of these different cultural, genetic and linguistic legacies are still present in Madagascar and other islands of the Indian Ocean. The close relationship between human migration and the introduction and spread of infectious diseases, a well-documented phenomenon, is particularly evident for the causative agent of leprosy, Mycobacterium leprae. In this study, we used whole-genome sequencing and molecular dating to characterize the genetic background and retrace the origin of the M. leprae strains circulating in Madagascar (n=30) and the Comoros (n=3), two islands where leprosy is still considered a public health problem and monitored as part of a drug resistance surveillance program. Most M. leprae strains (97%) from Madagascar and Comoros belonged to a new genotype as part of the branch 1, closely related to SNP-type 1D, named 1D-Malagasy. Other strains belonged to the genotype 1A (3%). We sequenced 39 strains from nine other countries, which together with previously published genomes amounted to 242 genomes that were used for molecular dating. Specific SNP markers for the new 1D-Malagasy genotype were used to screen samples from 11 countries and revealed this genotype to be restricted to Madagascar with the sole exception being a strain from Malawi. The overall analysis thus ruled out a possible introduction of leprosy by the Austronesian settlers, and suggests a later origin from East Africa, the Middle East or South Asia.